Kabaret as 'n 'Alternatiewe' Kommunikasieverrigting - Stephan Bouwer (Communicare)
In this article an attempt is made to examine cabaret, a sub-genre of Dra ma, as an "alternative" communication transaction. Firstly, reference is made to the actual theatrical perfor mance as two-way communication (vide, Inter alla, Keir Elam) between a "cluster" of senders ( theatrical collaborators) and the receivers (= audlence). The history of cabaret is related briefly, with special reference to certain conventions that were es tablished In Paris (1881) and the Ber lin cabaret of the Welmar Republic - e.g. cross-dressing and other shock tactics, in order to high-light the mes sage as such. Subsequently, cabaret as "protest art"- Is examined: It is noted that most definitions, ex pressed by various historians and theoreticians, stress the fact that cabaret, primarily, is protest art. It is postulated that senders often rely on the "sleeper effect" to get the mes sage across. The emotive term (in the South African context) "alternative" is discussed before an attempt is made to demonstrate that discourse "Intervention" can create new mes sages out of existing literature through Juxtapositions. This article is based on a paper that was read at the annual SACOMM conference on September 6, 1990 at the HSRC, Pretoria